Zoledronate for patients with invasive residual disease after anthracyclines-taxane-based chemotherapy for early breast cancer - The Phase III NeoAdjuvant Trial Add-oN (NaTaN) study (GBG 36/ABCSG 29) - Von Minckwitz, G.; Rezai, M.; Tesch, H.; Huober, J.; Gerber, B.; Zahm, D. M.; Hilfrich, J.; Costa, S. D.; Dubsky, P.; Blohmer, J. U.; Denkert, Carsten; Hanusch, C.; et al. (European Journal of Cancer, 2016)
BACKGROUND: Patients with invasive residual disease after neoadjuvant chemotherapy (NACT) are considered to have chemo-resistant breast cancer. Bisphosphonates are an established treatment for bone metastases and are of potential benefit as adjuvant treatment in early breast cancer. PATIENTS AND METHODS: Patients who had invasive tumour residuals (ypT1-4 and/or ypN+) after a minimum of four cycles of anthracycline-taxane-containing NACT were eligible for the NeoAdjuvant Trial Add-oN study. Patients were randomised within 3 years after surgery to receive zoledronate 4 mg i.v. for 5 years versus observation. Zoledronate was given every 4 weeks for the first 6 months, every 3 months for the following 2 years, and every 6 months for the last 2.5 years. Primary objective was disease-free survival. RESULTS: After a median time of 54.7 months no difference in disease-free survival was observed between the zoledronate and observation groups (hazard ratio [HR] 0.960, 95% confidence interval [CI] 0.709-1.30, log rank P=0.789). Various subgroups were examined without identifying a treatment effect of zoledronate. Patients over 55 years of age showed a HR of 0.832 in favour of zoledronate, but the result was not significant (P=0.480). A similar result was obtained for overall survival with a HR of 1.19 (95% CI 0.79-1.79; log rank P=0.408). Zoledronate was well tolerated and no new toxicity signal was identified. CONCLUSION: Postneoadjuvant treatment with zoledronate does not improve outcome in patients without pathological complete response after neoadjuvant anthracycline-taxane-based chemotherapy for early breast cancer.
EVALuna2:33068